Utilization of Technology Training to Improve Digital Skills of Elementary School Students - Winarni, Sri (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The use of technology in basic education is increasingly important to prepare students for the digital era. The aim of this research is to discuss the use of the Canva and Zoom platforms as tools in technology training to improve the digital skills of elementary school students. Through Canva, students are given the opportunity to develop creativity and visual understanding with graphic design, while Zoom becomes a virtual platform for remote training, deepening collaboration and communication skills. This technology training not only focuses on the technical aspects, but also provides a foundation for the development of 21st century skills. However, it is important to note that technology integration must take into account challenges and ethical aspects, while ensuring equal access and supporting students' holistic development. Proposing the use of Canva and Zoom in elementary schools can be a positive step in creating a generation that is ready to face dynamic changes in the digital world.